GERMAN GOVERNMENT REPRESENTATIVES VISIT USM TO EXPLORE OPPORTUNITIES FOR COOPERATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGE TOWN, PENANG, 4 March 2016 – A visit by representatives of Deutscher Akademischer Austausch Dienst (DAAD) or the German Academic Exchange Service and the German Embassy in Malaysia to the Universiti Sains Malaysia (USM) Main Campus recently aimed to explore opportunities for cooperation in academic studies, learning and research between USM and universities in Germany.